Student’s Problem-Solving Skills in Thermodynamics at Dampelas 1 Senior High School - Nadia Rahmah; Darsikin Darsikin (Universitas Lambung Mangkurat, 2021)
This study explores students' problem-solving skills in thermodynamics at Grade XI Science Senior High School 1 Dampelas. This research is a qualitative descriptive study. The research subjects consisted of 6 students was conducted in a high school in Dampelas. The research instrument used was a test of student’s problem-solving skills on thermodynamic based on Polya's problem-solving. Respondents consist of various cognitive abilities (high, medium, and low). They were also willing to do an interview. This study indicated that students' problem-solving skills on thermodynamic materials based on Polya's problem-solving steps in the